ANALISIS BUDAYA KERJA PEGAWAI PADA BAGIAN KEBERSIHAN DINAS PASAR DAN PENATAAN PEDAGANG KAKI LIMA (PKL) KOTA SAMARINDA* - Herliany Herliany (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
This research intends to investigate the work culture, constraints, and efforts to overcome constraints of personnel work culture at the Cleanliness Division of Market and Street Vendor Samarinda City Office. It is a descriptive, quantitative research. The research variable is the personnel work performance which comprises two indicators: attitude toward jobs and attitude toward work hours. The population is 30 people and 28 of them become the samples of this research. The data are gathered through literature study and field research by means of questionnaire, interview and direct observation. The data are then analyzed through importance-performance analysis. The research result shows that 95,42% respondents consider work culture “very important” and 75,37% respondents appraise it in “good category”. Based on this result, the writer recommends that: (a) two-way communication between the leaders and staff should always be conducted and the meetings among units / sub-units should be optimized; (b) leaders should send their staff to trainings or workshop related to cleanliness services; and (c) leaders should regularly evaluate the work culture effectiveness and efficiency.